Medium-Chain Triglyceride (MCT) Content of Adult Enteral Tube Feeding Formulas and Clinical Outcomes. A Systematic Review - Muscaritoli, Maurizio; Pradelli, Lorenzo (Frontiers in Nutrition, 2021)
Available data on the effect of lipid composition of enteral formulas on clinical outcomes are controversial. The present systematic review was performed in order to verify whether the presence of specific lipidic substrates, namely medium-chain triglycerides (MCT), in enteral tube feeding formulas is associated to measurable clinical benefits in patients receiving enteral nutrition in different clinical settings, including home enteral nutrition (HEN). The results of this systematic review highlight a lack of robust evidence supporting the use of specific types of lipids in standard or disease-specific formulas. Evidence exists, however, that MCT-containing formulas are safe and well tolerated. Further, well designed, adequately powered, randomized controlled trials would be needed in order to assess the superiority of MCT- containing enteral formulas over other standard or disease-specific commercially available enteral products.